2005
DOI: 10.1089/dia.2005.7.876
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump Therapy in Preschool Children with Type 1 Diabetes Mellitus Improves Glycemic Control and Decreases Glucose Excursions and the Risk of Hypoglycemia

Abstract: CSII in preschool children is feasible and safe. Pump therapy reduced the glycemic excursions and decreased hypoglycemia duration and frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 17 publications
2
42
0
4
Order By: Relevance
“…In particular, Inouye et al 27 demonstrated that recurrent hypoglycemia in rats with diabetes increases glucose consumption. Combining the assumption that these researchers' result would hold for type 1 diabetes patients with the well-established connection between hypoglycemia and glucose variability [28][29][30] provides a probable explanation for our findings.…”
Section: Discussionsupporting
confidence: 75%
“…In particular, Inouye et al 27 demonstrated that recurrent hypoglycemia in rats with diabetes increases glucose consumption. Combining the assumption that these researchers' result would hold for type 1 diabetes patients with the well-established connection between hypoglycemia and glucose variability [28][29][30] provides a probable explanation for our findings.…”
Section: Discussionsupporting
confidence: 75%
“…Insulin pumps lead not only to the improved glycemic profiles but in comparison with conventional medications, also limit the degree of hypoglycemia 23 . In our recent study we concluded that for this form of treatment, it is better to give priority to short duration insulin analogues (such as insulin aspart, Novorapid) than human insulin Actrapid 25 .…”
Section: Discussionmentioning
confidence: 99%
“…В аналогичных нерандомизированных крупных исследова-ниях, проведенных в мире и в РФ [11][12][13] с включением большого числа пациентов, также показано улучшение метаболического контроля заболевания -снижение НbA 1с и потребности в инсу-лине. Кроме того, было продемонстрировано снижение уровней среднесуточной гликемии и вариабельности ее показателей с уве-личением продолжительности эугликемии в динамических на-блюдениях при назначении помповой инсулинотерапии.…”
Section: результаты и их обсуждениеunclassified